Ambientalização universitária: o olhar dos estudantes da UFSCar para as questões ambientais - Vieira, Marisa Sartori (2015)
The process known as greening universities refers to the introduction of environmental issues in the teaching-research-extension and management fronts. Considering the various initiatives of the Federal University of São Carlos (UFSCar) insert the environmental education in the curricula and management, this study aimed to assess what form and how is this process in view of undergraduate students in chemistry and Pedagogy in three campuses UFSCar (São Carlos, Araras and Sorocaba). To this end, a virtual tool known as "Sustainability Test" was used (www.projetosustentabilidade.sc.usp.br) to assess sustainability practices in academic spaces. The themes analyzed in this study were divided in four categories: a) Environmental Management (waste management, water, energy, mobility / accessibility, green areas and green technologies); b) curriculum greening (environmental education in teaching / curriculum); c) Involvement and Participation d) The role of universities face to environmental issues. In addition to the questionnaire, interviews were conducted focus group type and consulted institutional legislation concerning the issue investigated. While acknowledging the Environmental Education (EE) in the institution, it was observed that most students of both courses were unaware of the actions related to environmental management, especially in the campus of San Carlos. The theme of "green technologies" still seemed far from the Education field, as well as the Science-Technology-Society-Environment Approach (CTSA). The main difficulty pointed out by students for their involvement in environmental issues is the lack of time and information, which may be a priority target given to the theme in these spaces. According to the data collected, the role of universities would be to invest in educational processes and disseminate scientific knowledge, approach the community, addressing EA critically. It was found that the promotion of reflection and dialogue between institutional subjects that carry different views on the greening of HEIs should be seen as necessary strategies to face the challenges inherent in such a process.